Oiling of the continental shelf and coastal marshes over eight years after the 2010 Deepwater Horizon oil spill. (September 2019) - Turner, R. Eugene; Rabalais, Nancy N.; Overton, Edward B.; Meyer, Buffy M.; McClenachan, Giovanna; Swenson, Erick M.; Besonen, Mark; Parsons, Michael L.; Zingre, Jeffrey
Abstract: We measured the temporal and spatial trajectory of oiling from the April, 2010, Deepwater Horizon oil spill in water from Louisiana's continental shelf, the estuarine waters of Barataria Bay, and in coastal marsh sediments. The concentrations of 28 target alkanes and 43 target polycyclic aromatic hydrocarbons were determined in water samples collected on 10 offshore cruises, in 19 water samples collected monthly one km offshore at 13 inshore stations in 2010 and 2013, and in 16–60 surficial marsh sediment samples collected on each of 26 trips. The concentration of total aromatics in offshore waters peaked in late summer, 2010, at 100 times above the May, 2010 values, which were already slightly contaminated. There were no differences in surface or bottom water samples. The concentration of total aromatics declined at a rate of 73% y −1 to 1/1000th of the May 2010 values by summer 2016. The concentrations inside the estuary were proportional to those one km offshore, but were 10–30% lower. The oil concentrations in sediments were initially different at 1 and 10 m distance into the marsh, but became equal after 2 years. Thus, the distinction between oiled and unoiled sites became blurred, if not non-existent then, and oiling had spread over an area wider than was visible initially. The concentrations of oil in sediments were 100–1000 times above the May 2010 values, and dropped to 10 times higher after 8 years, thereafter, demonstrating a long-term contamination by oil or oil residues that will remain for decades. The chemical signature of the oil residues offshore compared to in the marsh reflects the more aerobic offshore conditions and water-soluble tendencies of the dissolved components, whereas the anaerobic marsh sediments will retain the heavier molecular components for a long time, and have a consequential effect on the ecosystems. Graphical abstract: Image 1 Highlights: Oil concentrations on shelf and in marsh were followed for 8 years post DWH oil spill. Targeted aromatic concentrations peaked on shelf at 100 times above initial values. Targeted aromatics concentrations in offshore water declined after 2010 at 73% y −1 . Marsh sediment concentrations remain at 10 times higher than pre-spill conditions. Anaerobic soils retained heavier oil molecules that may have consequential ecological effect. Abstract : Measured concentration of alkanes and aromatics in shelf waters and marsh sediments over 8 years after the Deepwater Horizon oil spill. Molecular transformations described.